Prevalence of ocular morbidity in preschool children in Pune, Maharashtra - Sagar Kalamkar; Parikshit Madhav Gogate; Hardeep Kaur; Supriya Pramod Phadke; Amit Shinde (Journal of Clinical Ophthalmology and Research, 2022)
Purpose: The purpose of this study was to determine the prevalence of ocular morbidity in preschool children in Anganwadis of Pune. Methods: All preschool children from Anganwadi in the area of Vishrantwadi and Yerawada in Pune city, western India, in the age group 36 to <72 months, underwent comprehensive eye examination in October 2019–February 2020: visual acuity estimation of each eye separately, slit-lamp examination, cycloplegic refraction, orthoptic evaluation, and fundoscopy. Prior to screening, an informed written consent form was taken from their parents and class teacher. All children needing optical or medical care were provided the same. Results: We examined 1341 children (aged 3 to <6 years, mean: 3.85 ± 1.0) in 36 Anganwadis, and 693 (51.7%) were girls; 81 (6%) children were detected to have ocular morbidities. There were refractive error in 42 (3.1%), strabismus 8 (0.6%), disorder of lid and adnexa 11 (0.8%), allergic conjunctivitis 2 (0.15%), bacterial conjunctivitis 3 (0.2%), viral conjunctivitis 2 (0.15%), corneal opacity 3 (0.2%), nystagmus 4 (0.3%), convergence insufficiency 3 (0.2%), and cataract 2 (0.15%). There was no gender difference for any morbidity, but older children were more likely to have one (P < 0.001). Out of 42 having refractive error, 5/42 (12%) had myopia, 1/42 (2%) hypermetropia, 11/42 (26%) myopic astigmatism, 3/42 (7%) compound myopic astigmatism, and 22/42 (52%) had mixed astigmatism. Conclusion: Refractive error in preschool children was not an insignificant problem. Most of the morbidities were treatable, and visual impairment was preventable.